Rehabilitation nursing : a contemporary approach to practice - Mauk, Kristen L. (Sudbury, Massachusetts : Jone and Bartlett Learning, 2012)
Offers a clinically focused text designed to integrate rehabilitation into an academic curriculum, to educate nurses new to the specialty, and to aid practicing nurses preparing for certification. Incorporating competencies set forth by the Association of Rehabilitation Nurses (ARN), this resource includes key terms, learning objectives, case studies, critical thinking, personal reflection, resources, and Web links. --From publisher description.
Overview of rehabilitation -- Chronicity and disability -- Settings for care -- Theories and models -- The interdisciplinary rehabilitation team -- Nursing roles -- Improving nutritional status and swallowing -- Maintaining skin integrity -- Establishing bowel and bladder patterns -- Promoting mobility and function -- Enhancing cognition, communication, and behavior -- Addressing sexuality and disability -- Educating clients and families -- The art of caring : addressing psychosocial/spiritual issues : spirituality, coping, depression, grieving, adjustment, adaptation -- Stroke -- Brain injury -- Spinal cord injury -- Joint replacement -- Amputation -- Polytrauma -- Cardiac and pulmonary disease -- Neurological disorders -- Other chronic illnesses -- Cultural perspectives within rehabilitation nursing -- Ethical and legal issues -- Health policy, legislation, financing -- Pediatric rehab -- Geriatric rehab -- Animal assisted therapy -- Life care planning.
Includes index.
Keywords: REHABILITATION NURSING